2019
DOI: 10.3390/s19122835
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Precise Point Positioning with a Xiaomi MI 8 Android Smartphone

Abstract: The Global Navigation Satellite System (GNSS) positioning technology using smartphones can be applied to many aspects of mass life, and the world’s first dual-frequency GNSS smartphone Xiaomi MI 8 represents a new trend in the development of GNSS positioning technology with mobile phones. The main purpose of this work is to explore the best real-time positioning performance that can be achieved on a smartphone without reference stations. By analyzing the GNSS raw measurements, it is found that all the three mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 11 publications
(23 reference statements)
2
66
0
2
Order By: Relevance
“…Traditional travel diaries or travel survey data were mostly derived from household interviews or regional censuses [20]. Over the past decade, with the development of data collection from transit smart cards, GPS/GNSS [21][22][23], and mobile phones, direct travel trajectory data have been complementing or replacing conventional travel data at a rapidly increasing rate. These data help us to understand human travel behavior better by zooming into individuals' behaviors more closely than ever.…”
Section: The Study Of Travel Behaviormentioning
confidence: 99%
“…Traditional travel diaries or travel survey data were mostly derived from household interviews or regional censuses [20]. Over the past decade, with the development of data collection from transit smart cards, GPS/GNSS [21][22][23], and mobile phones, direct travel trajectory data have been complementing or replacing conventional travel data at a rapidly increasing rate. These data help us to understand human travel behavior better by zooming into individuals' behaviors more closely than ever.…”
Section: The Study Of Travel Behaviormentioning
confidence: 99%
“…Már az első kísérletek bizonyították, hogy az okostelefonokba épített GNSS-vevőkkel lehetséges a méter alatti pontosság elérése, illetve, hogy elsősorban az olcsó antennák miatt, 1 A 2019. évi Mérnökgeodézia Konferencián elhangzott előadás írásos változata a pontosság elmarad a professzionális geodéziai vevőkkel elérhető pontosságtól (Banville-Diggelen 2016). A Google bejelentése óta számos tanulmány készült, amelyekkel az elérhető pontosságot vizsgálták, és a kutatók többször is bizonyították, hogy elérhető a szubméteres pontosság (Chen et al 2019, Darugna et al 2019, Dabove-di Pietra 2019, Warnant et al 2018, Geng et al 2018…”
Section: Bevezetésunclassified
“…Surprisingly, the single-frequency PPP provided a better solution than the dual-frequency one [16,21]. After analyzing the characteristic of raw pseudorange and carrier phase observations, a modified PPP strategy was proposed by estimating separate clock biases for pseudorange and carrier phase observations [23]. The static PPP experiments with raw GPS, BeiDou, and Galileo data from Xiaomi Mi 8 under an open environment showed that the positioning errors in the north and east directions would converge to within 1 m in 30 s [23].…”
Section: Introductionmentioning
confidence: 99%
“…After analyzing the characteristic of raw pseudorange and carrier phase observations, a modified PPP strategy was proposed by estimating separate clock biases for pseudorange and carrier phase observations [23]. The static PPP experiments with raw GPS, BeiDou, and Galileo data from Xiaomi Mi 8 under an open environment showed that the positioning errors in the north and east directions would converge to within 1 m in 30 s [23]. When conducting RTK with raw GPS, Galileo, and GLObal NAvigation Satellite System (GLONASS) observations from Xiaomi Mi 8 under complex dynamic environments, the horizontal accuracy of 1.17 m was obtained but the solution tracks were still severely fluctuated [16].…”
Section: Introductionmentioning
confidence: 99%